Searches for other vacua. Part II. A new Higgstory at the cosmological collider - Anson Hook; Junwu Huang; Davide Racco (Journal of High Energy Physics)
Abstract The detection of an oscillating pattern in the bispectrum of density perturbations could suggest the existence of a high-energy second minimum in the Higgs potential. If the Higgs field resided in this new minimum during inflation and was brought back to the electroweak vacuum by thermal corrections during reheating, the coupling of Standard Model particles to the inflaton would leave its imprint on the bispectrum. We focus on the fermions, whose dispersion relation can be modified by the coupling to the inflaton, leading to an enhanced particle production during inflation even if their mass during inflation is larger than the Hubble scale. This results in a large non-analytic contribution to non-Gaussianities, with an amplitude fNL as large as 100 in the squeezed limit, potentially detectable in future 21-cm surveys. Measuring the contributions from two fermions would allow us to compute the ratio of their masses, and to ascribe the origin of the signal to a new Higgs minimum. Such a discovery would be a tremendous step towards understanding the vacuum instability of the Higgs potential, and could have fascinating implications for anthropic considerations.